Corporate Shares as Shares - Katz, Larissa (Modern Studies in Property Law, 2019)
In this chapter, I ask whether shares in corporations ought to command more attention within theories of property. Contemporary liberal property theorists typically take land (and sometimes goods) as the basic case of property. Shares tend to be left out of these accounts or treated as imitations or mutations of the basic case. Economists, for their part, have transformed the idea of ownership: ‘owner’ refers to the ultimate beneficiary of the value of assets. Shares are treated as a central case of property by those who take this approach. Shareholders are taken to own the corporation insofar as they are the ultimate beneficiaries of its value. In this chapter, I concede shares do not fit within the traditional property framework. This does not mean, however, that the traditional idea of property is obsolete and that a new property framework is in order.

Women in private international law - Keyes, Mary E. (Research Handbook on Feminist Engagement with International Law, 2019)
There has been almost no consideration of the position of women in private international law. There is very little published research applying a feminist analysis to, or even considering the position of women in, private international law. This field gives almost no attention to the particular interests, positions and experiences of women as subjects of the law, or the contribution of women as makers of the law. In the common law, private international law was largely developed in the 19th century, by male judges who were strongly influenced by commentary written exclusively by men. This chapter establishes that the apparently gender-neutral nature of private international law conceals profoundly ingrained assumptions about gender, in which the masculine is represented as a rational and sophisticated businessman, and the feminine is represented as a legally incapable wife. It then considers the gendered dimension of private international law in international family law, referring in particular to the regulation of international child abduction, international family property agreements, and international commercial surrogacy. Each of these examples demonstrates the differential impact of the law on women, indicating the need for greater awareness of and attention to gender. It concludes that while there have been some advances recently, particularly in terms of increased representation of women in making and commenting on private international law, there remains a great need for further research into the position of women as legal subjects and law-makers in this field.
Keywords: Private International Law; Woman